Structurally Redesigned Bioorthogonal Reagents for Mitochondria-Specific Prodrug Activation - Dzijak, Rastislav; Galeta, Juraj; Vázquez, Arcadio; Kozák, Jaroslav; Matoušová, Marika; Fulka, Helena; Dračínský, Martin; Vrabel, Milan (JACS Au, 2021)
The development of abiotic chemical reactions that can be performed in an organelle-specific manner can provide new opportunities in drug delivery and cell and chemical biology. However, due to the complexity of the cellular environment, this remains a significant challenge. Here, we introduce structurally redesigned bioorthogonal tetrazine reagents that spontaneously accumulate in mitochondria of live mammalian cells. The attributes leading to their efficient accumulation in the organelle were optimized to include the right combination of lipophilicity and positive delocalized charge. The best performing mitochondriotropic tetrazines enable subcellular chemical release of TCO-caged compounds as we show using fluorogenic substrates and mitochondrial uncoupler niclosamide. Our work demonstrates that a shrewd redesign of common bioorthogonal reagents can lead to their transformation into organelle-specific probes, opening the possibility to activate prodrugs and manipulate biological processes at the subcellular level by using purely chemical tools.